2023
DOI: 10.1002/sd.2598
|View full text |Cite
|
Sign up to set email alerts
|

How does policy coherence shape effectiveness and inequality? Implications for sustainable development and the 2030 Agenda

Abstract: During the formulation of the 2030 Agenda for Sustainable Development, many promoted policy coherence as a key tool to ensure achievement of the Sustainable Development Goals (SDGs) in a way that “leaves no one behind.” Their argument assumed that coherent policymaking contributes to more effective policies and supports over‐arching efforts to reduce inequality. As the 2030 Agenda reaches the halfway point, however, countries are falling short on many SDGs, particularly SDG 10 (reduce inequality). This study r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…However, we acknowledge that the overall aims and objectives stated within the individual policies of a broader governance framework do not necessarily translate into practice, as we demonstrated in preceding paragraphs of this discussion through several examples from our case study. Beyond our Panamaspecific examples, numerous studies have shown how efforts to design and implement holistic and integrative governance approaches, including efforts focusing on policy coherence, have failed to meet their stated objectives and, in some cases, yielded unintended and undesirable consequences (Khalilian et al, 2010;Allwood, 2013;Kelly et al, 2018;Vince, 2018;Browne et al, 2023). Therefore, focusing on the stated objectives of policy instruments might not reflect the reality of what actually takes place on the ground.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we acknowledge that the overall aims and objectives stated within the individual policies of a broader governance framework do not necessarily translate into practice, as we demonstrated in preceding paragraphs of this discussion through several examples from our case study. Beyond our Panamaspecific examples, numerous studies have shown how efforts to design and implement holistic and integrative governance approaches, including efforts focusing on policy coherence, have failed to meet their stated objectives and, in some cases, yielded unintended and undesirable consequences (Khalilian et al, 2010;Allwood, 2013;Kelly et al, 2018;Vince, 2018;Browne et al, 2023). Therefore, focusing on the stated objectives of policy instruments might not reflect the reality of what actually takes place on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the provided examples also help highlight the limits of policy coherence and our analysis, as securing policy outcomes is not just a matter of synergistic, holistic, integrative, or coherent policies but also a product of capacity, resources, and political will (OECD, 2021;Shawoo et al, 2023). Additionally, while it is generally agreed that consistency leads to coherence, and coherence leads to a higher likelihood that objectives will be achieved, there is no clarity or consensus on how much coherence is "good" or "sufficient" enough to guarantee a particular outcome (OECD, 2021;Browne et al, 2023). In other words, the interpretation of our results is largely based on the relative assessment of coherence (higher or lower, as opposed to coherent to guarantee policy outcomes or not) and the theoretical assumption that higher coherence leads to an increased likelihood that an objective will be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, unlike the general consensus that points to the need for policy coherence in addressing SDGs to improve inequality, one study reported that policy coherence can, in fact, worsen inequalities, and thus should not be sought as a panacea (Browne et al, 2023). Trade-offs will continue to persist, and these need to be minimized with complementary pro-poor and pro-environmental policies (Crentsil et al, 2020;Dyngeland et al, 2020), which can be costlier in the long run.…”
mentioning
confidence: 99%